PENGARUH SERVANT LEADERSHIP DAN JOB RESOURCES TERHADAP JOB SATISFACTION DAN WELLBEING YANG DIMEDIASI WORK ENGAGEMENT PADA KARYAWAN PERBANKAN DI JAKARTA BARAT - Aristo, Agra Bagus; Tanuwijaya, Justine; Tamara, Anna; Raihani, Irbah Ayu; Nor, Norzanah Mat (ITB AAS Indonesia Surakarta, 2024)
This research was conducted with the aim of analyzing the influence of servant leadership and job resources on job satisfaction and wellbeing mediated by work engagement. The data used in this study are primary data and collected by distributing questionnaires filled out by banking employees in West Jakarta. The sample collection method used a purposive sampling method of 165 samples. The data processing techniques used in this study are instrument testing such as validity and reliability tests as well as structural equation modeling (SEM) using SPSS and SmartPLS. The results showed that servant leadership has a positive effect on work engagement, servant leadership has a positive effect on job satisfaction, servant leadership has no positive effect on wellbeing, job resources has a positive effect on work engagement, job resources has a positive effect on wellbeing, job resources has a positive effect on job satisfaction, work engagement has a positive effect on job satisfaction, work engagement has a positive effect on wellbeing, servant leadership has a positive effect on job satisfaction mediated by work engagement, servant leadership has a positive effect on wellbeing mediated by work engagement, job resources has a positive effect on job satisfaction mediated by work engagement, job resources have a positive effect on wellbeing mediated by work engagement. Keywords: Servant Leadership, Job Resources, Work Engagement, Job Satisfaction, Wellbeing